Kualitas dan Daya Simpan Buah Jeruk Fremont (Citrus reticulate var. Fremont) yang Dipanen dari Tingkat Ketinggian Lahan yang Berbeda. - Maya Dewi Sulistyningrum; Slamet Susanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
The experiment was aimed to study the quality and shelflife of Fremont fruit harvested from different land elevation. Fruit were harvested according to orchard harvest criteria. The experiment used Randomized Complete Design, with the treatment of land elevation level i.e. 500 - 600 m, 600 - 700 m, 700 - 800 m above sea level. Land elevation level influence peel color, at the higher land elevation level the orange color on peel was more appeared. Land elevation level in the range of 500 - 800 m above sea level did nor affect firmness and total soluble solids (TSS) content in fruit juice at harvest time, however there was a tendency that higher acid and vitamin C content were observed in fruit of tree grown in the higher land elevation. The decrease on weight of fruit, fruit firmness, acid and vitamin C contents and increase of TSS content were observed during storage. The fruit of Fremont not be stored more than four weeks, because in this experiment, the fruit at four week after harvest experienced significant weight loss and severe peel shrinkage they resulted in unmarketable fruit.